Antecedents and Consequences of Cronyism in Organizations - Khatri, Naresh; Tsang, Eric W. K. (2003)
In this paper we discuss cronyism that exists between superiors and subordinates. Cronyism is defined as favoritism shown by the superior to his or her subordinate based on their relationship, rather than the latter's capability or qualification, in exchange for the latter's personal loyalty. We argue that two cultural antecedents, namely particularism and paternalism, give rise to strong ingroup bias and unreserved personal loyalty, which in turn lead to cronyism. We examine the consequences of cronyism at the individual level with respect to job satisfaction, organizational commitment, and ingratiation. We also discuss how cronyism affects performance, morale, and inertia at the organizational level. Cronyism can be observed in all cultures; however, its manifestation is likely to vary from one culture to another.
Keywords: personal loyalty; Paternalism; Particularism; outgroup; Ingroup bias; ingroup; Cronyism